A Feminist Study of the Childfree Trend in Generation Z: A Normative Review - Wijdatun Nabila; Hasna Al Jauza; Maryam Maryam; Hannisyah Hannisyah; Inas Nur Faizah; Farida Ummu Zahra; Alifah Alifah; Muya Saroh; Febryan Hidayat; Muttorik Alil Abasir (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
This study aims to investigate feminist perspectives on child-free trends in Generation Z from a normative point of view. The focus is to understand how feminism sees this phenomenon in the context of individual freedom, gender responsibility, and prevailing social norms. The research methods used are theoretical and qualitative analysis. Data was obtained through a literature study that included articles, books, and documents related to feminism, gender studies, and child-free trends. A qualitative approach was used to explore and analyze feminist views related to the childfree phenomenon in Generation Z. The results showed that feminist thinking towards the childfree trend in Generation Z reflects the complexity of the relationship between individual freedom and social norms. Feminism stresses the importance of recognizing that the decision not to have children is a legitimate choice for women, allowing them to pursue careers, self-development, and life exploration unfettered by traditional motherhood. Nevertheless, social norms that still reinforce the role of mothers and caregivers sometimes create pressure and stigma against women who choose the child-free path. Novelty/Novelty. This research makes a new contribution to the understanding of the complexity of child-free trends in Generation Z through a normative feminist lens. Her emphasis on the relationship between individual freedom, gender responsibility, and social norms provides deeper insight into the challenges and opportunities faced by women in navigating their life choices in contemporary society.